From the cradle to the web: the growth of “Sharenting”— a scientometric perspective - Cataldo, Ilaria (2022)
“Sharenting” is an internet trend in which parents report detailed information or repeatedly post pictures, videos, and other content about their children on social media. Due to the duality of sharenting, which takes place online but has offline consequences, it is essential to understand the implications of sharenting for real-world parenting and child development. The present work analyzes references in the existing literature and links among published articles to better understand sharenting, evidence for it, and major topics associated with it and to uncover the gaps in the literature. Citation analysis of the current literature mainly focuses on risks and benefits related to sharenting practices, especially for the children, and on ethical and privacy concerns. Future studies should investigate the psychological mechanisms that drive sharenting-related behaviors in parents and multidisciplinary approaches to the phenomenon. With a broader perspective on these issues, practitioners and professionals in family studies will be able to delineate guidelines for informative interventions to increase awareness about the causes and consequences of publicly sharing child content.